2022
DOI: 10.1186/s12958-022-00996-1
|View full text |Cite
|
Sign up to set email alerts
|

Usage and cost-effectiveness of elective oocyte freezing: a retrospective observational study

Abstract: Background The previous model-based cost-effectiveness analyses regarding elective oocyte cryopreservation remained debatable, while the usage rate may influence the cost per live birth. The aim of this study is to disclose the usage and cost-effectiveness of the planned cryopreserved oocytes after oocyte thawing in real-world situations. Methods This was a retrospective single-center observational study. Women who electively cryopreserved oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We noted that out of 558 women, live births were achieved by 196 women giving an average of 35%. The age-wise distribution was comparable mainly in three studies [ 15 , 16 , 22 ]; the reason being varied age-group distribution. In total, 24/50 (48%) women achieved live birth and on-going pregnancy in the age group less than 38 years and 20/94 (21%) in the age-group 38 years or older.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…We noted that out of 558 women, live births were achieved by 196 women giving an average of 35%. The age-wise distribution was comparable mainly in three studies [ 15 , 16 , 22 ]; the reason being varied age-group distribution. In total, 24/50 (48%) women achieved live birth and on-going pregnancy in the age group less than 38 years and 20/94 (21%) in the age-group 38 years or older.…”
Section: Resultsmentioning
confidence: 75%
“…To date, studies reporting outcomes in women returning to use their cryopreserved oocytes after social egg freezing are scarce [ 14 , 15 , 16 ]. Hence, we conducted this study with an objective to evaluate the outcomes of egg thaw at Guy’s Hospital, following social egg freezing and to compare our results with a comprehensive literature review of published data in order to provide evidence-based contemporaneous information to help women make an informed decision when planning to embark on social egg freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Any explanation should include the facts that some aspects of treatment have not yet been fully clari ed and that this in itself is a limitation at the present. 19 As a result of our municipal lectures on fertility in this study, two participants changed their life plan to suit their fertility and became pregnant spontaneously. We need to be able to de nitively improve the current issue, which is the di culty in obtaining education on fertility.…”
Section: Discussionmentioning
confidence: 94%
“…Doganay et al reported an average duration of hospital stay as two days for laparoscopy, 7.4 days for laparotomy, and 11 days antibiotics-only treatment [13]. Similarly, Yang et al [14] also showed a marked decrease in hospital stay (5.4 days vs 8.9 days; p <.001) and wound infections with laparoscopy compared to laparotomy. Regarding the complication rates Carlson et al found that a laparoscopic surgical approach was significantly associated with a lower risk of perioperative complications compared to open surgery [15].…”
Section: Discussionmentioning
confidence: 99%